Menguak Misteri Simbol X dan Kegagalan Rebranding Twitter: Analisis Semiotika Marketing Oswald - Pratiwi, Sefya Dian (Jurnal Media dan Komunikasi Indonesia, 2025)
Twitter's recent rebranding to X, replacing its iconic blue bird with the letter, stunned users and triggered a wave of negativity. This study examines this rebranding failure through a consumer brandscape concept of marketing semiotics lens. Primary data was gathered by directly observing Twitter's logo transformation content, complemented by secondary data from a literature review. To validate interpretations, short interviews with five loyal Twitter users were conducted. The study reveals that Twitter's transition to the X aimed to communicate a narrative of change, innovation, and progress, positioning itself as a super app. Contrary to this intention, loyal Twitter users interpreted X negatively, associating it with the dark web. Analysing this through consumer brandscape semiotics marketing, the failure is attributed to emotional and cultural tensions arising from the abrupt shift from Twitter's iconic blue bird symbol to the letter X. This identity change led to confusion, discomfort, and negative user reactions. The rebranding failure underscores Twitter's insufficient consideration of marketing semiotics, particularly within the consumer brandscape. The implication is that a successful rebranding necessitates a holistic approach, encompassing the entire semiotic marketing ecosystem, including considerations of culture, values, and brand legacy, to effectively convey identity changes to users.